1995
DOI: 10.1177/030802269505801211
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effectiveness of a Preoperative Education Programme for Total Hip Replacement Patients

Abstract: This study examined some effects of providing preoperative education to patients prior to their hospital admission for a total hip replacement. The preoperative education programmes are organised and presented by an occupational therapist with the assistance of a physiotherapist, an anaesthetist, an orthopaedic nurse and a dietician. The content includes information on preparation for surgery, what to expect of admission, surgery and rehabilitation, and how to prepare for discharge. A quasi-experimental desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 15 publications
0
41
0
2
Order By: Relevance
“…18 Any study to compare outcomes in patients having or not having preoperative education would be unethical. 13 Patients have the right to receive at least standard information about the procedure and to decide whether to participate in any such study or The efficacy of patient information sheets in wrist arthroscopy 87 not. 6 In our experimental group, patients who received specific information on the procedure and written instructions on postoperative care through a takehome leaflet had significantly better recovery after wrist arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…18 Any study to compare outcomes in patients having or not having preoperative education would be unethical. 13 Patients have the right to receive at least standard information about the procedure and to decide whether to participate in any such study or The efficacy of patient information sheets in wrist arthroscopy 87 not. 6 In our experimental group, patients who received specific information on the procedure and written instructions on postoperative care through a takehome leaflet had significantly better recovery after wrist arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the benefits of preoperative information have shown positive effects on outcomes such as decreasing anxiety, pain and increasing self-care (Devine 1992, Spalding 1995, Davidson & Degner 1997, Walker 2002). Davidson and Degner evaluated an educational intervention that aimed to empower men who were newly diagnosed with prostate cancer.…”
Section: Patients' Needs For Informationmentioning
confidence: 99%
“…However, little information is given about what the usual care actually comprises although, of course, such a concept would not be the same across different contexts. Although more recent studies continue to employ similar research designs in extending this knowledge base (Spalding, 1995;Gammon & Mulholland, 1996;Tooth et al, 1997;Lookinland & Pool, 1998), the notion of what constitutes the usual care continues to be nebulous. Shuldam (1999) has raised the issue of a general lack of detail about what usual preoperative education is comprised of, and questions the integrity of the findings from such experiments.…”
Section: Introductionmentioning
confidence: 99%